Impact of Bullying in Childhood on Adult Health, Wealth, Crime, and Social Outcomes - Wolke, Dieter; Copeland, William E.; Angold, Adrian; Costello, E. Jane (Psychological Science, 2013)
Bullying is a serious problem for schools, parents, and public-policymakers alike. Bullying creates risks of health and social problems in childhood, but it is unclear if such risks extend into adulthood. A large cohort of children was assessed for bullying involvement in childhood and then followed up in young adulthood in an assessment of health, risky or illegal behavior, wealth, and social relationships. Victims of childhood bullying, including those that bullied others ( bully-victims), were at increased risk of poor health, wealth, and social-relationship outcomes in adulthood even after we controlled for family hardship and childhood psychiatric disorders. In contrast, pure bullies were not at increased risk of poor outcomes in adulthood once other family and childhood risk factors were taken into account. Being bullied is not a harmless rite of passage but throws a long shadow over affected people’s lives. Interventions in childhood are likely to reduce long-term health and social costs.